Influence of Y2O3 nanoparticles on the twinning of single crystalline magnesium. (September 2017) - Mallmann, C.; Simar, A.; Ferrié, E.; Fivel, M.; Lilleodden, E.T.
Abstract: The influence of Y2 O3 nanoparticles introduced by Friction Stir Processing on the deformation of magnesium has been studied with microcompression testing of single-crystal pillars oriented favorably for tensile twinning. It was found that the nanoparticles lower the twin nucleation stress and affect the twin morphology, as well as mitigate the size effects usually observed in pure magnesium single-crystals. While single twin nucleation is consistently observed in pure magnesium pillars, multiple twins of identical variants are observed in the pillars with nanoparticles, having nucleated at the Y2 O3 particles. Consequently, the resultant twin–twin boundaries lead to an effective hardening. Graphical Abstract: